2009
DOI: 10.1021/ac902404v
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Column Coupling System To Operate Chromatographic Supports Closer To Their Kinetic Performance Limit and To Enhance Method Development

Abstract: A new hardware solution is proposed that allows one to automatically change the length of a chromatographic bed. The setup is based on the serial coupling of chromatographic columns using two rotor-stator valves (with N positions, N + 1 ports). Despite the use of a prototype setup requiring rather long connection tubing, only 9% loss in efficiency is observed for compounds with a retention factor above 4 compared to the efficiency expected on the basis of the individual column results. It has been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The author believes that integrating these column parameters in the simulation program will be helpful, especially for optimizing the separation conditions for complex samples where high peak capacities obtained by coupled column systems are needed [34,39,42]. In addition, integrating these column parameters in the simulation programs allows users to easily optimize both the gradient operational conditions and column types for HPLC and UPLC method development by using the user-friendly graphic user interface of the simulation program.…”
Section: Flow Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The author believes that integrating these column parameters in the simulation program will be helpful, especially for optimizing the separation conditions for complex samples where high peak capacities obtained by coupled column systems are needed [34,39,42]. In addition, integrating these column parameters in the simulation programs allows users to easily optimize both the gradient operational conditions and column types for HPLC and UPLC method development by using the user-friendly graphic user interface of the simulation program.…”
Section: Flow Studymentioning
confidence: 99%
“…Although several papers have been published on optimizing HPLC/UPLC methods for complex samples based on carefully characterized columns using the flow study method reported in this manuscript [34,42,43], these papers only characterized a few specific types of columns. As far as the author knows, this t r,error (%) = (t r,pre -t r,exp )/t r,exp × 100% All the gradient runs were conducted using XBridgeC18 columns packed with 3.5 µm particles with the pore size of 130 Å.…”
Section: Flow Studymentioning
confidence: 99%
“…This is illustrated using a practical example of an isocratic separation of a test mixture of diuretic compounds (Fig. 2) 9. The top chromatogram shows the separation on two serially connected columns with a total length of 20 cm operated close to the optimum linear velocity yielding 26 000 plates in a total analysis time of 19 min.…”
Section: Fixed‐length and Free‐length Isocratic Kinetic Plotsmentioning
confidence: 99%
“… Separation of a diuretic mixture obtained on a 20 cm (A) and 30 cm (B) long column operated at the maximum system pressure (Δ P max =800 bar), showing that use of a longer column yields similar separation efficiency, but in a shorter analysis time. Reprinted with permission from 9. …”
Section: Fixed‐length and Free‐length Isocratic Kinetic Plotsmentioning
confidence: 99%
“…Whereas in the field of HPLC significant efforts are conducted to improve the kinetic performance, i.e., by employing short columns packed with small (sub-2-micron) particles to increase separation speed [18] and by the application of column-coupling technology to increase the efficiency [19,20], while applying ultra-high-pressure conditions, the developments in IC have lagged behind. This was mainly due to the low rupture pressure of the membrane in the eluent generator [21].…”
Section: Introductionmentioning
confidence: 99%